HUBUNGAN SELF EFFICACY DENGAN KEMAMPUAN KOMUNIKASI SISWA KELAS V SDN 22 JEPPE’E KECAMATAN TANETE RIATTANG BARAT KABUPATEN BONE - Sudirman Sudirman; Sitti Rahmawati; Achmad Shabir (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2023)
This research is a quantitative research with a symmetrical correlational type of research that aims to determine whether or not there is a significant relationship between self-efficacy and the communication skills of Class V students at SDN 22 Jeppe'e, Tanete Riattang Barat District, Bone Regency. The research population was all fifth-grade students at SDN 22 Jeppe'e, Tanete Riattang Barat District, Bone Regency, totaling 53 students. The sampling technique in this study is non-probability, namely total sampling. Data were collected with a questionnaire instrument. Data analysis techniques using descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistics, it was obtained that self-efficacy had an average of 91.94 and a percentage of 73.56% in the good category, and students' communication skills had an average of 94.35 and a percentage of 75.48% in the good category. Based on the results of inferential statistical analysis, it was obtained t count of 6.82 and a t table with a significance of 5%. of 1.67528 so that t count ≥ t table. It can be concluded that there is a significant relationship between self-efficacy and the communication skills of Class V students at SDN 22 Jeppe'e, Tanete Riattang Barat District, Bone Regency.Keywords: Self Efficacy, Students' Communication Ability